Análisis contrastivo de la subtitulación vista desde dos prismas: el descriptivismo y el prescriptivismo - Anjana Martínez Tejerina (JoSTrans: The Journal of Specialised Translation)
The purpose of the present article is to describe subtitling from two opposite translation approaches. This contrast attempts to highlight the importance of erasing prescriptive ideas not only in order to use strategies based on dynamic equivalence, but also to fully accept and understand translation in general, and subtitling, as a restricted form of translation, in particular. The article is divided into four sections: (a) prescriptivism and its theoretical framework, with its most relevant aspects examined in relation to subtitling; (b) descriptivism and its theoretical framework, considered in relation to subtitling; (c) a contrastive chart that summarises the basic features of both approaches and allows the reader to compare them at a glance; (d) findings, in which conclusions are drawn and a personal view is stated.